Catalisadores de MgO-SiO2 : efeito dos promotores CaO e SrO na conversão de etanol - Laier, Letícia Oliveira (Universidade Federal de São Carlos, 2015)
The replacement of chemical products by renewable raw materials is an important factor for the emission control of CO2. Consequently, there is a great commercial interest in the conversion of ethanol into 1,3-butadiene. The 1,3-butadiene compound is used in the production of a variety of synthetic rubbers and one important example is butadiene-styrene rubber (SBR), which is used in the production of car tires. This work studied the modification of the acid-base properties of MgO/SiO2 bifunctional catalysts and the understanding of different methodologies used in the preparation of these materials for the conversion reaction of ethanol into 1,3-butadiene. MgO/SiO2 catalysts of varying amounts of magnesia/silica were prepared by four different methods: i) precipitation followed by the mixing of the oxides in a ball mill, ii) precipitation of MgO followed by its mixing with aerosil silica in a ball mill, iii) precipitation of MgO followed by the mechanical mixing of the oxides and iv) sol-gel. The catalysts were characterized by X-ray diffraction, CO2 Temperature Programmed Desorption, Scanning Electron Microscopy and Specific Surface Area. Catalytic tests showed that the highest selectivities for 1,3 -butadiene were observed for the (MgO/SiO2) coprecipitation method and oxides mixed in a ball mill. The TPD-CO2 results demonstrate the formation of basic sites with the addition of SiO2 to MgO and the density of basic sites presents a great variation in the ratio MgO: SiO2. The catalyst MgO/SiO2 (5:1) was the most active and selective for 1,3-butadiene. The addition of CaO or SrO these catalysts have not resulted in increased selectivity for the formation of butadiene, but observed an increase in the acid properties, possibly due to non-inclusion of these oxides in MgO lattice and later the formation of basic sites of the type MgO-Mg-O-Si.
Keywords: Oxidos metálicos; Oxido alcalino-terrosos; Óxido de magnésio; Sílica; OUTROS